MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP SISWA DALAM MATERI SEGITIGA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) BERBANTUAN AUTOGRAPH DI KELAS VII SMP SANTO ANTONIUS JAKARTA - Maslina Simanjuntak (MES: Journal of Mathematics Education and Science, 2018)
Abstract. The purpose of this research is to improve the understanding of junior high school student class VII-2 of Santo Antonius Jakarta. The method used is class activity observation using think-pair-share (TPS) learning model with the help of autograph. The result shows a classical achievement on the first cycle with 86.7 % with average of 72.43, increase of students that reach the mastery learning achievement criteria of 26 students, increase in classical achievement of 86.67 %, average increase of 56.6 % and there's 19 students with medium increase of understanding, 11 students with high increase of understanding. Teacher's ability on executing the learning process on the first cycle is already categorized as good with 82.81, student observation result is also categorized as good eith 85.35. Keywords: Concept Undersranding, Think Pair Share, Autograph.